PERANCANGAN MULTIMEDIAINTERAKTIF PEMBELAJARAN GAMBAR TEKNIK MESIN UNTUK KELAS XI MENGGUNAKANAUTOCAD PADA SMK WISUDHA KARYA KUDUS - Rifky Hadi Ihsan; Efendi Efendi (STEKOM PRESS, 2018)
Multimedia-based learning media is a method of learning that can interact with its users besides having animated explanations of material. The problem at SMK Wisudha Karya Kudus about learning mechanical engineering drawings using AutoCAD is the difficulty of understanding the tools in the AutoCAD application, it becomes unattractive and difficult to understand the material in the teaching and learning process. The purpose of this research is to create an interactive learning media for machine engineering drawings using AutoCAD semesters I and II as media to assist student learning processes, providing alternative learning media to help teachers choose the right learning model for students. This type of research method uses the R&D method, the methods used include descriptive, evaluative and experimental methods. Descriptive method is used to collect data about existing conditions, evaluative methods are used to evaluate the trial process of developing a product and the experimental method is used to test the efficacy of the product produced. The results of this study are application programs, applications that have been designed can be used as an alternative to solving problems in SMK Wisudha Karya Kudus. By using electronic media in learning media, the benefits of creating alternative solutions from existing problems, namely in the form of Machine Engineering Image Learning Application, are able to provide complete video tutorials according to the basic competencies that the authors take from the source of mechanical engineering drawing books.